(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
The present examination Self-idea and Achievement Motivation of Secondary School Students was explored to discover the connection between Self-idea and Achievement Motivation of Secondary School Students. Information for the investigation were gathered utilizing Self-idea Questionnaire created by Raj Kumar Saraswath (1984) and Achievement Motive Test (ACMT) created by V.P. Bhargava (1994). The examiner utilized basic arbitrary testing procedure for choosing the example. The example comprises of 250 secondary school understudies. For investigating information ’t’ test, ANOVA and Pearson’s item minute co-proficient connection were the factual methods utilized. Discovering demonstrates that there is a critical connection between self-idea and accomplishment inspiration of secondary school understudies.